2020
DOI: 10.1105/tpc.20.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin CYCA3;4 Is a Postprophase Target of the APC/CCCS52A2 E3-Ligase Controlling Formative Cell Divisions in Arabidopsis

Abstract: The Anaphase Promoting Complex/Cyclosome (APC/C) controls unidirectional progression through the cell cycle by marking key cell cycle proteins for proteasomal turnover. Its activity is temporally regulated by the docking of different activating subunits, known in plants as CELL DIVISION PROTEIN 20 (CDC20) and CELL CYCLE SWITCH 52 (CCS52). Despite the importance of the APC/C during cell proliferation, the number of identified targets in the plant cell cycle is limited. Here, we used the growth and meristem phen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…CYCAs of the subgroups 1 and 2 were also enriched in G2/M cells, including CYCA2;4, which was not detected previously in CSCs. By contrast, two CYCAs of subgroup 3, CYCA3;1 and CYCA3;2, were depleted in G2/M cells, whereas CYCA3;4 showed no significant enrichment in G2/M cells, confirming recent data (36). CYCA3;3 was not detected, as expected for a meiosis-specific cyclin gene (33).…”
Section: Transcriptome Analysis Of Cells In G2/m Captures Cell Cycle Expressionsupporting
confidence: 84%
“…CYCAs of the subgroups 1 and 2 were also enriched in G2/M cells, including CYCA2;4, which was not detected previously in CSCs. By contrast, two CYCAs of subgroup 3, CYCA3;1 and CYCA3;2, were depleted in G2/M cells, whereas CYCA3;4 showed no significant enrichment in G2/M cells, confirming recent data (36). CYCA3;3 was not detected, as expected for a meiosis-specific cyclin gene (33).…”
Section: Transcriptome Analysis Of Cells In G2/m Captures Cell Cycle Expressionsupporting
confidence: 84%
“…For example, triploid poplar can promote the leaf size by affecting the expression of growth hormone, transcription factors and cell differentiation-related genes [38,39]. The complexity of anaphase promoting complex (APC) and the cell cycle switch (CCS52B) can selectively degrade regulatory protein factors that limit cell division, thus regulating the cell cycle [40,41]. We have identified that the Arabidopsis PCNA2 homologous gene is highly expressed in Pd, which can form a complex PCNA/CycD with D-cyclin to regulate the cell cycle [42].…”
Section: Discussionmentioning
confidence: 99%
“…SAMBA is an APC/C negative regulator that also interacts with A-type cyclins (CYCA2;2 and CYCA2;3, weakly with CYCA1;1) and promoted plant growth when mutated [ 89 ]. CYCA3;4 is targeted for proteasomal degradation by APC/C CCS52A2 , and plants with increased CYCA3;4 levels showed disorganized formative divisions, with defects in root meristem and leaf cell differentiation [ 90 ].…”
Section: Regulators Of Cdk Activitymentioning
confidence: 99%